Plasma Total Cysteine and Cardiovascular Risk Burden: Action and Interaction - Benedetta De Chiara; Valentina Sedda; Marina Parolini; Jonica Campolo; Renata De Maria; Raffaele Caruso; Gianluigi Pizzi; Olga Disoteo; Cinzia Dellanoce; Anna Rosa Corno; Giuliana Cighetti; Oberdan Parodi (The Scientific World Journal)
We hypothesized that redox analysis could provide sensitive markers of the oxidative pathway associated to the presence of an increasing number of cardiovascular risk factors (RFs), independently of type. We classified 304 subjects without cardiovascular disease into 4 groups according to the total number of RFs (smoking, hypertension, hypercholesterolaemia, hyperhomocysteinaemia, diabetes, obesity, and their combination). Oxidative stress was evaluated by measuring plasma total and reduced homocysteine, cysteine (Cys), glutathione, cysteinylglycine, blood reduced glutathione, and malondialdehyde. Twenty-seven percent of subjects were in group 0 RF, 26% in 1 RF, 31% in 2 RF, and 16% in ≥3 RF. By multivariable ordinal regression analysis, plasma total Cys was associated to a higher number of RF (OR = 1.068; 95% CI = 1.027–1.110, 𝑃=0.002). Total RF burden is associated with increased total Cys levels. These findings support a prooxidant effect of Cys in conjunction with RF burden, and shed light on the pathophysiologic role of redox state unbalance in preclinical atherosclerosis.